The Life of Ibn Ḥanbal - Ibn al-Jawzī, Abū al-Faraj ʻAbd al-Raḥmān ibn ʻAlī, approximately 1116-1201 (Book collections on Project MUSE., 2016)
"Ahmad ibn Hanbal (d. 241 H/855 AD), renowned for his profound knowledge of hadiths--the reports of the Prophet's sayings and deeds--is a major figure in the history of Islam. He was famous for living according to his own strict interpretation of the Prophetic model and for denying himself the most basic comforts, even though his family was prominent and his city, Baghdad, was then one of the wealthiest in the world. Ibn Hanbal's piety and austerity made him a folk hero, especially after he resisted the attempts of two caliphs to force him to accept rationalist doctrine. His subsequent imprisonment and flogging is one of the most dramatic episodes of medieval Islamic history, and his principled resistance influenced the course of Islamic law, the rise of Sunnism, and the legislative authority of the caliphate. [This book] is a translation of the biography of Ibn Hanbal by the Baghdad preacher, scholar, and storyteller Ibn al-Jawzi (d. 597 H/1200 AD), newly abridged for a paperback readership by translator Michael Cooperson. Set against the background of fierce debates over the role of reason and the basis of legitimate government, it tells the formidable life tale of one of the most influential Muslims in history."--